1999
DOI: 10.1002/etc.5620181018
|View full text |Cite
|
Sign up to set email alerts
|

Validity and ecological relevance of an active in situ bioassay using gammarus pulex and limnephilus lunatus

Abstract: In situ bioassays using aquatic organisms serve as a link between laboratory and field studies. However, the ecological relevance of in situ studies had not previously been assessed by direct comparison with field data. In this study, an in situ bioassay employing Gammarus pulex L. (Crustacea: Amphipoda) and Limnephilus lunatus Curtis (Insecta: Trichoptera) was used in two agricultural tributaries and the connecting headstream. Simultaneously, the short-term insecticide contamination and the stream population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 41 publications
2
46
0
1
Order By: Relevance
“…However, technical problems, such as clogging of mesh or vandalism to test chambers, restrict the wide application of in situ testing methods. It has also been shown that animals caged in the field are prevented from using avoidance behavior [3], and as a result, these tests may overestimate actual field toxicity.…”
Section: Evaluation Of In Situ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, technical problems, such as clogging of mesh or vandalism to test chambers, restrict the wide application of in situ testing methods. It has also been shown that animals caged in the field are prevented from using avoidance behavior [3], and as a result, these tests may overestimate actual field toxicity.…”
Section: Evaluation Of In Situ Resultsmentioning
confidence: 99%
“…Several attempts were made to link survival of in situ exposed freshwater and estuarine organisms to agricultural pollution [4,5], and some studies were able to detect pesticide effects using in situ testing [6][7][8]. However, a link of responses in situ and reactions of populations in the field has rarely been established [3].…”
Section: Introductionmentioning
confidence: 99%
“…Benthic invertebrates are highly exposed to contaminated sediments through their habitat choice and feeding habits. Previous research has shown that sediment contamination results in lower densities of amphipods (e.g., [15]). A possible explanation for this observation is that amphipods can actively leave contaminated sites by drifting processes [15].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the physical properties of the spray A considerable amount of research has been conitself, crop characteristics such as height, the amount of ducted on the development and optimization of open area between trees, diffuse noninterceptance, and air-assisted orchard sprayers during recent decades leaf area index influence the production and extent of (Hislop, 1991). However, drift from orchard sprayers pesticide that may be subject to drift (USEPA, 1999). remains an important environmental problem.…”
mentioning
confidence: 99%